Towards a more reliable historical reanalysis: Improvements for version 3 of the Twentieth Century Reanalysis system. (23rd August 2019) - Slivinski, Laura C.; Compo, Gilbert P.; Whitaker, Jeffrey S.; Sardeshmukh, Prashant D.; Giese, Benjamin S.; McColl, Chesley; Allan, Rob; Yin, Xungang; Vose, Russell; Titchner, Holly; Kennedy, John; Spencer, Lawrence J.; et al.
Abstract : Historical reanalyses that span more than a century are needed for a wide range of studies, from understanding large‐scale climate trends to diagnosing the impacts of individual historical extreme weather events. The Twentieth Century Reanalysis (20CR) Project is an effort to fill this need. It is supported by the National Oceanic and Atmospheric Administration (NOAA), the Cooperative Institute for Research in Environmental Sciences (CIRES), and the U.S. Department of Energy (DOE), and is facilitated by collaboration with the international Atmospheric Circulation Reconstructions over the Earth initiative. 20CR is the first ensemble of sub‐daily global atmospheric conditions spanning over 100 years. This provides a best estimate of the weather at any given place and time as well as an estimate of its confidence and uncertainty. While extremely useful, version 2c of this dataset (20CRv2c) has several significant issues, including inaccurate estimates of confidence and a global sea level pressure bias in the mid‐19th century. These and other issues can reduce its effectiveness for studies at many spatial and temporal scales. Therefore, the 20CR system underwent a series of developments to generate a significant new version of the reanalysis. The version 3 system (NOAA‐CIRES‐DOE 20CRv3) uses upgraded data assimilation methods including an adaptive inflation algorithm; has a newer, higher‐resolution forecast model that specifies dry air mass; and assimilates a larger set of pressure observations. These changes have improved the ensemble‐based estimates of confidence, removed spin‐up effects in the precipitation fields, and diminished the sea‐level pressure bias. Other improvements include more accurate representations of storm intensity, smaller errors, and large‐scale reductions in model bias. The 20CRv3 system is comprehensively reviewed, focusing on the aspects that have ameliorated issues in 20CRv2c. Despite the many improvements, some challenges remain, including a systematic bias in tropical precipitation and time‐varying biases in southern high‐latitude pressure fields. Abstract : A significant new version of the Twentieth Century Reanalysis data assimilation system, 20CRv3, has been developed. The 20CRv3 dataset will provide an ensemble of sub‐daily global atmospheric conditions spanning at least 180 years by assimilating only surface pressure observations into a coupled atmosphere–land forecast model. The new 20CRv3 system improves upon the previous system in several notable ways, including the use of upgraded data assimilation methods, a newer and higher‐resolution forecast model, and a larger set of available pressure observations.